Older adults as victims and witnesses - Brank, Eve M. (The Oxford handbook of developmental psychology and the law, 2024)
The older adult population is one of the fastest growing in the United States due to advances in medicine and aging baby boomers. Developmentally, bodies and minds go through changes as they age that contribute to victimization risk and eyewitness accuracy. Although official crime statistics suggest that older adults are infrequently crime victims, they may fear being victimized at a greater rate than other age groups and they are at increased risk of being victimized by family members who are entrusted to care for them. Older adults who are victimized or who witness another crime can be called upon to serve as an eyewitness. Eyewitness research that has focused on older adults as eyewitnesses has found that they generally do not perform as well as younger adults due to both developmental and generational differences. Using older adults in research requires creativity and extra efforts, but it is a worthwhile pursuit, given their potential for victimization and other involvement in the legal system.